Kurikulum Merdeka dalam Konsepsi Pendidikan Syekh Nawawi Al-Bantani - Fradana, Heru (Revorma: Jurnal Pendidikan dan Pemikiran, 2024)
Education is one of the ways to advance human civilization. Historical records reveal that the better education during a particular period, the better civil society developed. A dynamic development in education is needed to create a better civilization. In the era of globalization, education has a heavier task than ever before, the boundaries of space and time are no longer known in this era. The ease of access to information has both positive and negative impacts. While it is beneficial for knowledge, the incoming facts may not be filtered according to the culture and norms of a particular region or country, resulting in the loss of character and national identity. In this regard, the Ministry of Education provides a solution of the form of a learning curriculum, namely the "Merdeka Curriculum." The Merdeka Curriculum is expected to preserve the nation's character in the next generation. However, the question arises as to whether this curriculum concept aligns with Islamic values, given that Indonesia currently has a Muslim majority. This article discusses the theory of the Merdeka Curriculum from the perspective of Islamic education, as seen through the thoughts of one of the prominent scholars of the Indonesian archipelago who gained global recognition, namely Syekh Nawawi Al-Bantani. This academic article employs a qualitative approach using a literature review method to analyze Syekh Nawawi's views on the concept of the Merdeka Curriculum. The conclusion drawn from this study is that Syekh Nawawi's thinking emphasizes lifelong learning for a sustainable future and character education that builds uniqueness, identity, and national character. Keywords: Curriculum; Medeka Curriculum; Islamic Education; Syekh Nawawi Al-Bantani